(untitled) (Bangladesh Journal of Nuclear Medicine, 2021)
Primary hyperparathyroidism (PHPT) presenting as pathological fractures with brown tumors is very rare in children. The rarity and variable presentation of PHPT can make its diagnosis a challenge – especially in the developing countries where malnutrition may mask hypercalcemia. We report a case of a 14–year-old girl who presented with muscle pain, multiple fractures and bone pain. Laboratory tests revealed normocalcemia with vitamin D insufficiency. Subsequent biochemical, radiographic and scintigraphic findings were consistent with primary hyperparathyroidism due to a parathyroid adenoma. Tumor resection was done in a local hospital and histopathology confirmed parathyroid adenoma. Following parathyroidectomy, fractures were treated conservatively with supplementation of calcium and vitamin D. We found her quite capable of self-care and walking in good health at 1 year follow up. Though rare, PHPT-causing brown tumors related skeletal fractures is an important differential diagnosis in the evaluation of patients presenting with multiple foci of radiotracer uptake in bone scintigraphy. Bangladesh J. Nuclear Med. 22(2): 130-136, Jul 2019